2008
DOI: 10.1186/1471-2458-8-245
|View full text |Cite
|
Sign up to set email alerts
|

Viral hepatitis and HIV-associated tuberculosis: Risk factors and TB treatment outcomes in Thailand

Abstract: Background: The occurrence of tuberculosis (TB), human immunodeficiency virus (HIV), and viral hepatitis infections in the same patient poses unique clinical and public health challenges, because medications to treat TB and HIV are hepatotoxic. We conducted an observational study to evaluate risk factors for HBsAg and/or anti-HCV reactivity and to assess differences in adverse events and TB treatment outcomes among HIV-infected TB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…Some of these associations, such as the use of illicit drugs (Sirinak et al 2008), history of incarceration (Richards et al 2006), and HIV infection (Reis et al 2011), have been observed previously in Asia and the Americas.…”
Section: Discussionmentioning
confidence: 95%
“…Some of these associations, such as the use of illicit drugs (Sirinak et al 2008), history of incarceration (Richards et al 2006), and HIV infection (Reis et al 2011), have been observed previously in Asia and the Americas.…”
Section: Discussionmentioning
confidence: 95%
“…The major risk factors for triple infection of HIV-TB-Hepatitis were found to be having multiple sexual partners, followed by unsafe sexual intercourse (data not presented). This is probably due to shared routes of transmission of HIV and hepatitis (B&C), and TB is the opportunistic disease which comes after immune suppression like in HIV patients (Sterling and Sulkowski, 2004;Sy and Jamal, 2006;Solomon et al, 2008;Sirinak et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, certain studies disagree with this association, possibly because they were conducted with a small number of patients with the hepatitis B or C viruses 37,38,39,40 .…”
Section: Discussionmentioning
confidence: 99%